Impact of Endophytic and Rhizospheric Fungi on The Growth and Specialised Metabolite Production of Phyllanthus niruri L. - Winda Nawfetrias; Yuda Purwana Roswanjaya; Nur Alfi Saryanah; Sulastri Sulastri; Lukita Devy; Rizkita Rachmi Esyanti; Ahmad Faizal (Tropical Life Sciences Research, 2025)
Medicinal plants are rich sources of specialised metabolites, crucial for various fields like agriculture, forestry, food processing, biofuels and environmental remediation. Microbes, particularly endophytic and rhizospheric fungi, play a significant role in optimising the production and regulation of these compounds. Several research showed these fungi in various plants, but they have not been thoroughly studied in Phyllanthus niruri, especially to promote growth and elicit lignan compounds like phyllanthin in P. niruri. A total of 131 fungi, consist of 57 rhizospheric fungi and 74 endophytic fungi, were successfully isolated from P. niruri in six different lowland areas in West Java. The potency assay results indicated that 106 fungi could produce indole-3-acetic acid (IAA). Six fungi could synthesise cellulase, and one fungus had the capability to solubilise phosphate. Our results showed that Fusarium sp., Colletotrichum gloeosporioides, Colletotrichum tenuissimum, Colletotrichum fructicola, Pseudallescheria boydii, Aspergillus aculeatus, Myrothecium inundatum, Colletotrichum truncatum can synthesise IAA. Fusarium sp. and Myrothecium inundatum could synthesise cellulase and only Aspergillus aculeatus have activity as phosphate solubilisation.Cocultivation of P. niruri and eight endophytic and rhizospheric fungi showed that Fusarium sp., C. gloeosporioides, P. boydii, A. aculeatus and M. inundatum had the potential traits to increase biomass, phyllanthin levels and phyllanthin yield. In general, these fungi have the potency to be elicitors to enhance phyllanthin in P. niruri.